Dynamic Time History and Pushover Analysis of Special Truss Moment Frames by Using Eurocodes - Setvatishayesteh, Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Special Truss Moment Frames (STMFs)were introduced in USA (1994) as a new system alternative to ordinary Truss Moment Frames (TMF). STMFs are resistant to both gravity and lateral loads over long spans and AISC 341-10 has all the necessary design procedures. STMF design procedures are not available in Eurocodes. Therefore, the main objective of this research was to investigate STMF by using Eurocodes and European steel sections. A numerical study was undertaken to study the seismic behaviour of (STMFs) using dynamic time history and pushover analysis. Performance-based Plastic Design (PBPD) methodology was used to design the STMF based on Eurocode 8 and in some parts AISC 341-10 code was used. Seismostruct software was used to design frames with 4, 7 and 10 stories and to investigate parameters, such as, maximum base shear, drift story, capacity curve and also performance criteria (chord rotation) according to Eurocodes through extensive nonlinear dynamic analysis for an appropriate number of ground motion records. In second phase, a set of nonlinear static (pushover) analysis carried out to find the capacity curve, base shear and story drifts. In the third phase, SAP2000 was used to find performance limit state of STMF and TMF and the results were compared together. In fourth phase, the behaviour factor of STMFs was calculated and compared with the behaviour factor of other structural framing systems. The results obtained were compared with the results of similar frames from past literature. Overall, the results confirmed the validity of the proposed framing system by meeting all the performance design objectives, such as, target drifts and intended yield mechanism. Generally, nonlinear analysis do not required the structural performance check after PBPD and this can be considered as an advantage. Keywords: STMF, PBPD, Dynamic time history, pushover, performance criteria

ÖZ: Özel Kafes Moment Çerçeveler (ÖKMÇ) 1994 yılında ABD’de sıradan Kafes Moment Çerçeveler’e (KMÇ) alternatik yeni bir sistem olarak sunulmuştur.ÖKMÇ uzun açıklıklı düşey ve yatay yüklere dirençli bir sistemdir ve AISC-10’da tüm gerekli tasarım prosedürleri vardır.Fakat ÖKMÇ tasarım prosedürleri Avrupa Standardlarında yoktur.Bu nedenle, bu araştırmanın ana hedefi Avrupa Standardları ve Avrupa çelik kesitlerini kullanarak ÖKMÇ’yi incelemektir.ÖKMÇ’ninsismik davranışını dinamikzamantarihveitme analizikullanarak incelemek için bir nümerik çalışma yapıldı.Performansa Dayalı Plastik Tasarım(PDPT) yöntemi kullanılarak ÖKMÇ’nin Avrupa Standardı 8’e göre tasarımı yapılmış ve bazı kısımlarda ise AISC 341-10 standardı kullanılmıştır.Seismostruct yazılımı 4, 7 ve 10 katlı çerçeveleri tasarlamak ve en yüksek taban kesme kuvveti, kat sürüklenmesi, kapasite eğrisi ve performans kriteri (acor rotasyonu) için kullanılmıştır. Bu tasarım Avrupa Standardına göre yapılmış ve de yeterli derecede ve/sayıda yer hareketi kayıtları kullanılarak yapılmıştır. İkinci kısımda kapasite eğrisini, taban kesme kuvvetini ve sürüklenme oranını elde etmek için bir dizi doğrusal olmayan statik (itme) analiz yapıldı.Üçüncü kısımda SAP2000 kullanılarak ÖKMÇ ve sırada KMÇperformans sınır durumu incelenmiş ve sonuçlar karşılaştırılmıştır.Dördüncü kısımda ÖKMÇ davranış katsayısı hesaplanmış ve diğer yapısal çerçeve sistemlerinin davranış katsayıları ile karşılaştırılmıştır.Elde edilen sonuçlar ayrıca literatürden benzer çerçeve sonuçları ile karşılaştırılmıştır. Tümünde elde edilen sonuçlar önerilen sistemin performans tasarım hedeflerini, örneğin, hedef sürüklenme ve amaçlanan verim mekanizmasını sağladığını onaylamaktatır. Genelde, doğrusal olmayan analizlerde, performansa dayalı plastik tasarım yöntemi kullanıldıktan sonra, yapısal performans çekinin yapılmasına gerek yoktur.Bu da bir avantaj olarak düşünülebilir. Anahtar kelimeler: ÖKMÇ, KMÇ, PDPT, Dinamikzamantarih, itme, performans kriteri
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Assist. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering; Metal buildings-Design and construction; STMF; PBPD; Dynamic time history; pushover; performance criteria